Achieve of Marketing Superiority under the adoption of the concept of internal marketing: Applied Research at National Company for Insurance Company. (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The insurance Sector of important vessels saving that work on the accumulation of capitals which contribute to the financing of economic and social development plans of countries, in order to achieve of marketing superiority in presenting the insurance services it would require insurance companies focus their marketing efforts and increased interest in internal customer to recruitment new customers and keep of current customers, so the research aims to release the impact of the dimensions of the internal marketing of (the company's vision, training and development, incentive and, motivation, internal communication) in the dimensions of the marketing superiority (to keep the customer, service quality, customer satisfaction, customer, value, marketing innovation) through sampling of (64) officials in the national insurance company, Question nairnnare is used as a main instrument for collecting data and in formation from the sample, their answer were analyzed by using SPSS at calculating arithmetic means standard deviations, (F) test and coefficient of correlation (R2). The research reached several conclusions of which:• The sample member's response to dimensions of internal marketing was in the medium degree, but responding to the dimensions of marketing superiority was in the high degree.• 2. There is an effect of moral meaning of internal marketing in dimensions of marketing superiority the degree is (67%).